2005
DOI: 10.4049/jimmunol.175.5.3287
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α-Dependent and -Independent Maturation of Dendritic Cells and Recruited CD11cintCD11b+ Cells during Oral Salmonella Infection

Abstract: Maturation of dendritic cells (DC) is crucial for their ability to induce adaptive immunity. Although several mediators of DC maturation have been found, their contributions to DC maturation during infection are poorly understood. In this study we show that murine conventional (CD11chigh) DC up-regulate costimulatory molecules in a subset-specific manner after oral Salmonella infection. Although both CD8α+ and CD8α− subsets increase CD86 expression, CD40 was preferentially up-regulated on CD8α+ DC, and CD80 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
114
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 57 publications
(118 citation statements)
references
References 54 publications
3
114
1
Order By: Relevance
“…The unique Ag-presenting capacity of the CD8a -CD11b + DC subset in MLN described in the present study may be another complexity of DC in GALT. Moreover, this DC subset in MLN has been shown to take up Salmonella after oral infection with this microbe [15]. Although a recent study demonstrated that CD8a -CD11b -DC in Peyer's patches take up viral Ag from apoptotic cells and cross-present it to cognate T cells, this population did not appear to be a major cross-presenting APC in the present study [20].…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…The unique Ag-presenting capacity of the CD8a -CD11b + DC subset in MLN described in the present study may be another complexity of DC in GALT. Moreover, this DC subset in MLN has been shown to take up Salmonella after oral infection with this microbe [15]. Although a recent study demonstrated that CD8a -CD11b -DC in Peyer's patches take up viral Ag from apoptotic cells and cross-present it to cognate T cells, this population did not appear to be a major cross-presenting APC in the present study [20].…”
Section: Discussioncontrasting
confidence: 69%
“…Although CD8a -CD11b + DC, CD8a + CD11b -DC and B220 + plasmacytoid DC (PDC) are present in every secondary lymphoid tissue, there is an additional double-negative population (CD8a -CD11b -) in LN that is not dominant in spleen and a double-positive subset (CD8a + CD11b + ) that represents a major population only in LN other than mesenteric LN (MLN) [5,6]. A number of experimental models, most performed with splenic DC, suggest that each subset serves a unique role in the immune system [2,[6][7][8][9][10][11][12][13][14][15][16]. Moreover, CD8a + and CD8a -splenic DC have different gene-expression profiles, a finding that strongly supports a functional difference between these two subsets [17].…”
Section: Introductionmentioning
confidence: 99%
“…Tissue lysates and serum were prepared as described previously [4]. Concentrations of CCL2, CXCL9 and CXCL2 in PP and MLN extracts, serum samples and sorted cell populations were determined using either the Opt EIA Elisa kit (BD) or mouse cytokine bead array (CBA) kit (BD Biosciences) for CCL2.…”
Section: Measurements Of Chemokines By Elisa or Cytokine Bead Arraymentioning
confidence: 99%
“…Murine monocytes in the blood are a heterogeneous population and have been divided into two main subsets based on whether they are present in steady state or recruited under inflammatory conditions [1]. Inflammatory Gr-1 hi CCR2 hi CX 3 CR1 low monocytes, which have also been called TipDC upon entering a tissue, are a source of molecules important in controlling bacterial infection, particularly iNOS and TNF-a [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation